Translation and Ideology: A Study of Lin Zexu’s Translation Activities - Chen, Shunyi (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2017)
This paper describes a brief study of Lin Zexu’s translation activities from the perspective of ideology. Lin was not a translator himself, but an initiator and patron of translations. He organised translation activities with sources from foreign newspapers and books to help his anti-opium campaign and resistance to British invasion. Translations from foreign sources were not welcomed by the Qing government and translators were even regarded as traitors. Lin, however, had a contrasting attitude towards translation. To Lin, translation was a way to learn about the outside world and to learn from it. The Qing government, on the other hand, held the view that translations of foreign documents were of little use. The difference between Lin’s view and that of the Qing court can be seen as an ideological divergence between Lin and the government he served. This culminated in the expulsion of Lin from the government, his exile and the termination of his translation activities. This shows how a state instigated ideological position can predominate over an oppositional ideology – in this case to the detriment of the state.